Charcot neuroarthropathy after simultaneous pancreas-kidney transplantation (SPKT) - Rangel, Erika Bevilaqua; Gomes, Samirah Abreu; Sá, João Roberto de; Melaragno, Cláudio Santiago; Carvalho, Aluízio; Salzedas, Alcides; Linhares, Marcelo Moura; Gonzalez, Adriano Miziara; Medina-Pestana, José Osmar (Brazilian Journal of Transplantation, 2008)
Charcot's neuroarthropathy was initially described in Tabes Dorsalis, but it occurs more frequently in diabetic patients. Its pathogenesis includes (a) sensory neuropathy; loss of sensation leading to recurrent microfractures, (b) motor neuropathy; muscle atrophy and weakness that alter pressure points in joints leading to trauma and ulcers and finally (c) autonomic neuropathy; which result in increased local blood flow with arteriovenous shunts and bone resorption, which in turn leads to dislocations, sub-luxations and micro-fractures.1,2 The triggering event is usually traumatic, although not always reported by patients, with usually unilateral involvement. In the acute phase, the foot is hot and swollen, painful or not, and may present with erythema. In the chronic phase, there is foot deformity associated with collapse of the plantar arch, calluses and ulcers. At our center, we observed a 4.6% incidence of de novo Charcot neuroarthropathy in the TSPR (median: 10 months), with the main risk factor being the weight-adjusted cumulative dose of the steroid in the first six months of transplantation.3 We report one case in a 42-year-old female patient with clinical and radiological findings six months after TSPR (Figures 1 and 2). The diagnosis of Charcot's neuroarthropathy is clinical and should include X-ray (look for changes in the “5 D's”: joint distension, displacement, debris, disorganization and increased density), bone scintigraphy with technetium and/or nuclear magnetic resonance. Treatment can be clinical (immobilization and medications that inhibit bone resorption) or surgical, depending on the severity of the condition.1,2,4